2017
DOI: 10.1108/ijrdm-10-2016-0193
|View full text |Cite
|
Sign up to set email alerts
|

Mall image, shopping well-being and mall loyalty

Abstract: Purpose This study was carried out to identify mall image dimensions, analyse and discuss how shopping well-being is influenced by mall image and impacts on mall loyalty with the moderating role of gender differences. Besides, the relationship between hedonic value (HV) and utilitarian value (UV) on shopping well-being are investigated. The paper aims to discuss these issues. Design/methodology/approach Through a questionnaire, data were obtained from shoppers at the biggest and the most remarkable malls in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 124 publications
3
19
0
1
Order By: Relevance
“…Selected papers also highlighted that purchases (online or offline) led to consumer happiness (Bastos and Brucks 2017; Shafiee and Es-Haghi 2017; Sramova and Pavelka 2019). Handayani et al (2018) posited that in addition to purchasing, malls and shopping centers also represent enjoyment.…”
Section: Thematic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Selected papers also highlighted that purchases (online or offline) led to consumer happiness (Bastos and Brucks 2017; Shafiee and Es-Haghi 2017; Sramova and Pavelka 2019). Handayani et al (2018) posited that in addition to purchasing, malls and shopping centers also represent enjoyment.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Handayani et al (2018) posited that in addition to purchasing, malls and shopping centers also represent enjoyment. The literature depicts that consumers consider offline shopping as a source of fun and pleasure (shopping well-being; Shafiee and Es-Haghi 2017). Marshall (2019) concluded that young consumers enjoy shopping in convenience stores and that the ambience of a space appeals to the sense of well-being.…”
Section: Thematic Analysismentioning
confidence: 99%
“…Mall loyalty relates to “shoppers’ intentions to repatronize a specific mall, make purchases and recommend the mall to others” (Chebat et al , 2009, p. 54) and is an outcome of various experiential aspects, including mall atmospherics (Chebat et al , 2014; Michon et al , 2015), shopping values (Djelassi et al , 2018; Rahman et al , 2016), presence of friends (Merrilees and Miller, 2019), engaging in pleasurable activities (Mohammad Shafiee and Es-Haghi, 2017) and excitement (Baker and Wakefield, 2012). Mall loyalty is a long-term behavioral intention toward the holistic complex of the mall (Vilnai-Yavetz et al , 2021) and as such serves in our study as an indicator of the impact of the absence of mall experiences and as a criterion to predict the resiliency of malls in the new marketplace.…”
Section: Theoretical Background and Core Conceptsmentioning
confidence: 99%
“…The concept of well-being refers to general life satisfaction and emotional intensity or, in other words, the happiness and satisfaction of people with their lives (Larsen et al , 1985). Shoppers’ well-being is affected by experiential mall characteristics such as retail offerings, functionality, convenience, safety, atmosphere, design, incorporation of greenery, mall image, leisure and services (El Hedhli et al , 2013; Maggioni et al , 2019; Rosenbaum et al , 2016; Mohammad Shafiee and Es-Haghi, 2017) as well as shopper characteristics such as decision styles, shopping values, self-congruity, self-identification and gender (El Hedhli et al , 2013; El Hedhli et al , 2016; Maggioni et al , 2019; Mohammad Shafiee and Es-Haghi; 2017). Well-being is an indicator at the individual level that reflects the short-term reaction of shoppers to the absence of mall experiences.…”
Section: Theoretical Background and Core Conceptsmentioning
confidence: 99%
See 1 more Smart Citation